2021
DOI: 10.3390/jmse9060566
|View full text |Cite
|
Sign up to set email alerts
|

Ship AIS Trajectory Clustering: An HDBSCAN-Based Approach

Abstract: The Automatic Identification System (AIS) of ships provides massive data for maritime transportation management and related researches. Trajectory clustering has been widely used in recent years as a fundamental method of maritime traffic analysis to provide insightful knowledge for traffic management and operation optimization, etc. This paper proposes a ship AIS trajectory clustering method based on Hausdorff distance and Hierarchical Density-Based Spatial Clustering of Applications with Noise (HDBSCAN), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 29 publications
0
42
0
3
Order By: Relevance
“…It calculates the maximum value of the shortest distance from a point on one trajectory to all points on the other trajectory. Wang et al [39] found that the Hausdorff distance has an optimal effect when measuring the shape similarity between trajectories. However, as the Hausdorff distance must calculate the minimum value of the distance between a point and all points of the other trajectory, and does not consider the time sequence, the calculation efficiency is low and cannot identify the direction of motion.…”
Section: Related Researchmentioning
confidence: 99%
“…It calculates the maximum value of the shortest distance from a point on one trajectory to all points on the other trajectory. Wang et al [39] found that the Hausdorff distance has an optimal effect when measuring the shape similarity between trajectories. However, as the Hausdorff distance must calculate the minimum value of the distance between a point and all points of the other trajectory, and does not consider the time sequence, the calculation efficiency is low and cannot identify the direction of motion.…”
Section: Related Researchmentioning
confidence: 99%
“…To begin, Wang et al and Lee et al have researched maritime traffic route extraction. In the study of Wang et al, the Douglas-Peucker algorithm was used to simplify the trajectory of the ship, and the hierarchical trajectory was clustered using Hierarchical DBSCAN (HDBSCAN) [17]. The study by Lee et al extracted density-based routes by analyzing 90% of maritime traffic with kernel density estimation (KDE) based on a geographic information system (GIS).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the DBSCAN algorithm has better applicability than other algorithms because it can identify the trajectories of different shapes and has the ability to identify anomalies [25,26]. Lee et al [27] segmented ship trajectories and clustered the sub-trajectories using the DBSCAN algorithm.…”
Section: Introductionmentioning
confidence: 99%